Molecular Mechanisms That Contribute to Bone Marrow Pain - Ivanusic, Jason J. (Frontiers in Neurology, 2017)
Pain associated a bony pathology puts a significant burden on individuals, society, and the health care systems worldwide. Pathology that involves the bone marrow activates sensory nerve terminal endings of peripheral bone marrow nociceptors, and is the likely trigger for pain. This review presents our current understanding of how bone marrow nociceptors are influenced by noxious stimuli presented in pathology associated with bone marrow. A number of ion channels and receptors are emerging as important modulators of the activity of peripheral bone marrow nociceptors. Nerve growth factor sequestration has been trialed for the management of inflammatory bone pain (osteoarthritis), and there is significant evidence for interaction of nerve growth factor with bone marrow nociceptors. Activation of transient receptor potential cation channel subfamily V member 1 sensitizes bone marrow nociceptors and could contribute to increased sensitivity of patients to noxious stimuli in a variety of bony pathologies. Acid sensing ion channels sense changes to tissue pH in the bone marrow microenvironment and could be targeted to treat pathology that involves acidosis of the bone marrow. Piezo2 is a mechanically gated ion channel that has recently been reported to be expressed by most myelinated bone marrow nociceptors and might be a target for treatments directed against mechanically induced bone pain. These ion channels and receptors could be useful targets for the development of peripherally acting drugs to treat pain of bony origin.